Running Ms-DOS / The Microsoft Guide to Getting the Most Out of the Standard Operating System for the IBM PC and 50 other Personal Computers - Wolverton Van (Microsoftpress, 1985)
An inside book at the software that tells your computer how to think. Acknowledgements, Introduction, Getting to Know DOS, Learning to Use DOS, Quick Reference to DOS Commands, Glossary, Index.